A high performance direct carbon solid oxide fuel cell – A green pathway for brown coal utilization. (15th August 2019) - Wu, Hao; Xiao, Jie; Zeng, Xiaoyuan; Li, Xue; Yang, Jing; Zou, Yuling; Liu, Sudongfang; Dong, Peng; Zhang, Yingjie; Liu, Jiang
Graphical abstract: Here we report a high-performance direct carbon solid oxide fuel cell that enables a green pathway for brown coal utilization. Highlights: Brown coal of China is used as fuel for direct carbon solid oxide fuel cells. Abundant Ca element exists in brown coal fuel and is beneficial to anode reaction. Brown coal char has larger specific surface area and more pores than the raw coal. The cell with brown coal char has a maximum power density of 221 mW cm −2 at 850 °C. The cell with brown coal char reveals a higher carbon fuel utilization. Abstract: Direct carbon solid oxide fuel cells (DC-SOFCs) are promising, all-solid-state, highly efficient and environment-friendly power generating devices fueled by solid carbons. In addition, utilization of real-world coal as fuel for DC-SOFC is an attractive topic, however, they still yield poor performance due to negative effect of impurities in coal. In order to utilize brown coal to generate electricity efficiently and environmentally, here we report a high-performance direct carbon solid oxide fuel cell that enables a green pathway for brown coal utilization. The cell consists of nano Al2 O3 doped yttria-stabilized zirconia (YSZ) electrolyte supports and Ag-Gd0.1 Ce0.9 O2-δ as symmetrical composite catalyst electrodes. Fueled with raw brown coal and brown coal char at 850 °C separately, the cells can achieve maximum power densities of 211.4 and 221 mW cm −2, respectively. Furthermore, a stable discharging voltage and platform with the fuel utilization of 61.5% are demonstrated when brown coal char fueled DC-SOFC is operated under a constant current of 0.1 A.